Between the archive imperative and the bandeirante rhetoric: The constitution of a scientific knowledge for the invention of the Paulista - Anhezini, Karina [UNESP] (2021)
This text analyzes the history of the construction of a knowledge established through the assembly of an archive. This knowledge will be presented by analyzing a course on bandeirologia (the science of expeditions towards inner country), offered in 1946 in the city of São Paulo. During the narrative, the reader will come across fragments of archival gestures and the repetition of statements that resulted in the constitution of a bandeirante (explorer) rhetoric. Such discourse was committed to provide a new historicity for Brazil, creating and making believe in a History of Brazil dependent on and grounded in events delimited by the history of São Paulo’s expeditions to the countryside.